Compounds from Lactobacillus plantarum culture supernatants with potential pro-healing and anti-pathogenic properties in skin chronic wounds - Ramos, Alberto (2015)
Context: It is necessary to advance the field of alternative treatments for chronic wounds that are financially accessible to the least economically developed countries. Previously we demonstrated that topical applications of Lactobacillus plantarum culture supernatants (LAPS) on human-infected chronic wounds reduce the pathogenic bioburden, the amount of necrotic tissue, and the wound area, as well as promote debridement, granulation tissue, and wound healing. Objective: To study LAPS chemically and biologically and to find potential molecules responsible for its pro-healing and anti-pathogenic properties in chronic wounds. Materials and methods: (1) Chemical analysis: extracts were subjected to a column chromatography and the fractions obtained were studied by GCMS. (2) Quantification: dl-lactic acid (commercial kit), phenolic compounds (Folin?Ciocalteu), H2O2 (micro-titration), and cations (flame photometry). (3) Biological analysis: autoinducers type 2 (AI-2) (Vibrio harveyi BB170 bioassay), DNAase activity (Agar DNAase), and Pseudomonas aeruginosa biofilm inhibition (crystal violet technique). Results: According to its biological activity, the most significant molecules found by GCMS were the following: antimicrobials (mevalonolactone, 5-methyl-hydantoine, benzoic acid, etc.); surfactants (di-palmitin, distearin, and 1,5-monolinolein); anesthetics (barbituric acid derivatives), and AI-2 precursors (4,5-dihydroxy-2,3-pentanedione and 2-methyl-2,3,3,4-tetrahydroxytetrahydrofurane). Concentrations measured (µg/mL): dl-lactic acid (11.71 ± 1.53) and H2O2 (36 ± 2.0); phenolic compounds (485.2 ± 15.20); sodium (370 ± 17); potassium 920 ± 24); calcium (20 ± 4); and magnesium (15 ± 3). DNAase from LAPS had activity on genomic DNA from PMNs and P. aeruginosa. Discussion and conclusion: The molecules and biological activities found in LAPS could explain the observed effects in human chronic wounds.